Age‐related changes in mean corpuscular volumes in patients without anaemia: An analysis of large‐volume data from a single institute. Issue 12 (22nd May 2022) - Lee, Jin Young; Choi, Hanlim; Park, Jin Woo; Son, Bo Ra; Park, Jong Hyock; Jang, Lee Chan; Lee, Jae Gil
Abstract: Although the mean corpuscular volume (MCV) has been associated with various diseases, these associations in relation to the age‐related trends in MCV remain unclear. Therefore, we used a dataset with over one million values to identify the relationship between ageing and MCV changes. All laboratory data obtained between November 1998 and November 2019 at Chungbuk National University Hospital were retrospectively collected. After excluding cases with missing values for individual complete blood count parameters, outlier MCV values, and ages less than 1 year and more than 88 years, 977, 335 MCV values were obtained from 309, 393 patients. Principal component analysis of blood components with ages and analysis of the median value changes for each blood component across decade‐wise age groups were conducted to identify relationships between ageing and changes in blood components. The median values of MCV showed gradual increments with age. The linear relationship for patients aged 1–25 years had a larger slope than that for patients aged 26–88 years. For MCV, the equation for patients aged 1–25 years was 0.40*(age) + 81.24 in females and 0.45*(age) + 79.58 in males. The equation for patients aged 26–90 years was 0.04*(age) + 88.97 in females and 0.06*age + 88.30 in males. Among patients aged >40 years, the MCV value was higher in men than in women. Analysis of a large dataset showed that the MCV gradually increased with age and the linear relationship differed between patients aged 1–25 and 26–88 years.